2022
DOI: 10.3390/ijms23147502
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing and CRISPR/Cas9 Gene Editing of Enterotoxigenic Escherichia coli BE311 for Fluorescence Labeling and Enterotoxin Analyses

Abstract: Some prevention strategies, including vaccines and antibiotic alternatives, have been developed to reduce enterotoxigenic Escherichia coli proliferation in animal production. In this study, a wild-type strain of BE311 with a virulent heat-stable enterotoxin gene identical to E. coli K99 was isolated for its high potential for gene expression ability. The whole genome of E. coli BE311 was sequenced for gene analyses and editing. Subsequently, the fluorescent gene mCherry was successfully knocked into the genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…As a modified ETEC strain, E. coli BE311-mCherry attaches to the IPEC-J2 cells via adhesins and subsequently releases enterotoxins, causing cellular barrier damage and inflammation. 15 Our study results are in line with earlier findings, demonstrating that L. plantarum T10 and L. plantarum T13 can decrease the production of IL-8 and TNF-α in IPEC-J2 cells following infection with E. coli BE311-mCherry. A previous study showed that Lactobacillus spp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a modified ETEC strain, E. coli BE311-mCherry attaches to the IPEC-J2 cells via adhesins and subsequently releases enterotoxins, causing cellular barrier damage and inflammation. 15 Our study results are in line with earlier findings, demonstrating that L. plantarum T10 and L. plantarum T13 can decrease the production of IL-8 and TNF-α in IPEC-J2 cells following infection with E. coli BE311-mCherry. A previous study showed that Lactobacillus spp.…”
Section: Discussionsupporting
confidence: 93%
“…The enterotoxigenic Escherichia coli (ETEC) strain BE311-mCherry with red-fluorescing mCherry protein was constructed in the previous study. 15 The strain was cultivated in Luria-Bertani (LB) broth in shake culture at 37 °C and was used in constructing a cellular infection model. Porcine intestinal epithelial cells (IPEC-J2) were obtained from Hunan Fenghui Biotechnology Co., Ltd (Hunan, China).…”
Section: Lactobacilli Strains and Intestinal Epithelial Cellsmentioning
confidence: 99%
“…l -isoleucine is referred to as a branched chain amino acid together with l -valine and l -leucine. It is a high-value-added amino acid with muscle repair function, which is also often used to treat cirrhosis, obesity, coma, and other conditions. l -isoleucine has received much attention in recent years as a synthetic precursor for the antiglycolytic drug 4-hydroxyisoleucine. , Fermentation is the primary method for industrial production of l -isoleucine; meanwhile, chemical synthesis and extraction from hair also play a key role in its production. Additionally, metabolic engineering of the l -isoleucine biosynthesis pathway in Corynebacterium glutamicum and E. coli has also been widely used for the industrial production of this amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…It is a high-value-added amino acid with muscle repair function, which is also often used to treat cirrhosis, obesity, coma, and other conditions. 1 4 l -isoleucine has received much attention in recent years as a synthetic precursor for the antiglycolytic drug 4-hydroxyisoleucine. 5 , 6 Fermentation is the primary method for industrial production of l -isoleucine; meanwhile, chemical synthesis and extraction from hair also play a key role in its production.…”
Section: Introductionmentioning
confidence: 99%